Kajian mengenai kemahiran metakognitif di kalangan pelajar-pelajar sekolah menengah di Malaysia dalam menyelesaikan masalah fizik - Sulaiman, Seth; Abdullah, Fatin Aliah Phang (Faculty of Education, 2005)
The aim of the study was to determine the relationship between metacognitive skills and problem solving skills in physics among form four physics students in secondary schools in Johor. A sample of 1300 student respondents were selected from nine districts in Johor . The districts are Batu Pahat, Muar, Kota Tinggi, Pontian, Johor Bahru, Segamat, Mersing, Kulai and Kluang. The sample consisted of 625 male and 660 female students while 15 respondents somehow did not state their sex thus considered as missing values. Two well-validated instruments namely Metacognitive Skills Questionnaire (MSQ) and Physics Problem Solving Ability Test (PPSAT) were conducted and the data collected were analyzed using SPSSPC software. Descriptive statistics- means, standard deviation, percentages and inferential statistics khi square, one way ANOVA and Pearson-r and ttest were used for interpreting the data. Findings of the study revealed that there was a weak but significant correlation (Î±=0.01) between metacognitive skills and Physics problem solving ability of the respondents. However, students with high metacognitive skills had mean score on PPSAT which was significantly different from those students with moderate and weak metacognitive skills (Î±=0.01). There was no significant difference in Problem solving skills between students with moderate and weak metacognitive Skills. Further results indicated that there was significant difference in means of problem solving ability among Chinese, Malay and Indian Students in favour of the Chinese students and also between rural and urban schools in favour of rural schools. There was no significant difference between Malay and Indian students in problem solving ability. For metacognitive skills there was a significant gender difference in means in favour of female students and significant difference in means in favour of urban schools. Implications of the study and suggestions for further research were also being discussed.